Community mediation in Malaysia: The challenges faced by community mediators and the DNUI - Hanna Ambaras, Khan; Nora, Abdul Hak (Universiti Putra Malaysia, 2015)
The Department of National Unity and Integration (DNUI) designed community mediation programmes to provide mediation as a method of dispute resolution to be adopted at community level. The Department trained “Ahli Jawatankuasa Rukun Tetangga” (Neighbourhood Committee Members) to be community mediators. The objective of this paper is to study the challenges faced by these community mediators in practising and subsequently, providing mediation services to the community as well as the challenges faced by the Department in supporting the community mediators. The authors adopted the qualitative research method to gather data in writing this paper. From the data collected, it was found that community mediation programmes are new, the mediators were yet to be recognised widely in Malaysia, there was not enough promotion and the funds allocated for the programme were limited. These are the challenges faced by both the community mediators and the Department. It is suggested that the community mediation programme in Malaysia be given a proper centre and administrative structure in each state so as to ensure that the programme is administered by an appropriate body that will overcome all challenges, allowing the programme to succeed.